Energy Harvesting: Electric Field Assisted Microfluidic Platform for Generation of Tailorable Porous Microbeads as Cell Carriers for Tissue Engineering (Adv. Funct. Mater. 20/2018). (14th May 2018) - Costantini, Marco; Guzowski, Jan; Żuk, Paweł J.; Mozetic, Pamela; De Panfilis, Simone; Jaroszewicz, Jakub; Heljak, Marcin; Massimi, Mara; Pierron, Maxime; Trombetta, Marcella; Dentini, Mariella; Święszkowski, Wojciech; et al.
Abstract : A novel preparation method for porous microbeads of tuneable size and internal porous texture is described in article number 1800874 by Piotr Garstecki, Andrea Barbetta, and co‐workers. An oil‐in‐water emulsion is generated inside a flow‐focusing microfluidic device. An electric field breaks up the emulsion into mesoscopic double droplets, that in turn serve as a template for the porous microbeads. The microbeads are effective cell carriers.